2021
DOI: 10.3390/ijms22147622
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids: Fuelling the Fire of Atherosclerosis or Therapeutic Extinguishers?

Abstract: Glucocorticoids are steroid hormones with key roles in the regulation of many physiological systems including energy homeostasis and immunity. However, chronic glucocorticoid excess, highlighted in Cushing’s syndrome, is established as being associated with increased cardiovascular disease (CVD) risk. Atherosclerosis is the major cause of CVD, leading to complications including coronary artery disease, myocardial infarction and heart failure. While the associations between glucocorticoid excess and increased p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 134 publications
(157 reference statements)
0
26
0
Order By: Relevance
“…Moreover, the treatment for SSc patients with atherosclerosis is knotty due to the role of glucocorticoid therapy in atherosclerosis being highly controversial. 16 A previous study suggested that low-dose prednisone did not increase the risk of atherosclerosis. 17 Recent studies demonstrated glucocorticoid was associated with a dose-dependent increase in risk of cardiovascular events, even low-dose glucocorticoid increases the risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the treatment for SSc patients with atherosclerosis is knotty due to the role of glucocorticoid therapy in atherosclerosis being highly controversial. 16 A previous study suggested that low-dose prednisone did not increase the risk of atherosclerosis. 17 Recent studies demonstrated glucocorticoid was associated with a dose-dependent increase in risk of cardiovascular events, even low-dose glucocorticoid increases the risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 97%
“…At present, the treatment mainly focuses on protecting the function of organs and improving the quality of life of patients without specific preventive and treatment measures. Moreover, the treatment for SSc patients with atherosclerosis is knotty due to the role of glucocorticoid therapy in atherosclerosis being highly controversial 16 . A previous study suggested that low‐dose prednisone did not increase the risk of atherosclerosis 17 .…”
Section: Discussionmentioning
confidence: 99%
“…They lead to a direct endothelial cell dysfunction by promoting the production of vasoconstrictors acting on the smooth muscle cells. In addition, some other pre-clinical experimental models suggest an increased accumulation of macrophages in atherosclerotic lesions, with an increased cholesterol esterification [32]. Altogether, long term GC exposure is associated with increased atherosclerosis.…”
Section: Ischemic Events In Gca 21 Implicated Mechanismsmentioning
confidence: 92%
“…On one hand, some preclinical studies showed that GC exposure may reduce the recruitment of monocytes and macrophages within the atherosclerotic lesions and reduce the cholesterol accumulation in macrophages. It also results in a reduction of macrophage-induced pro-inflammatory cytokine release limiting the vascular remodeling [32]. On the other hand, GC are also implied in pro-atherogenic mechanisms.…”
Section: Ischemic Events In Gca 21 Implicated Mechanismsmentioning
confidence: 99%
“…Rarely, Cushing’s Syndrome is caused by primary bilateral macronodular adrenal hyperplasia or primary pigmented nodular adrenocortical disease and its non-pigmented variant: isolated micronodular adrenocortical disease [ 11 ]. Both types of Cushing’s Syndrome (CS) result in excessive adrenal cortisol secretion which binds to the glucocorticoid receptors (GRs), leading to increased morbidity and mortality [ 12 ]. Importantly, modern data suggest that the clinical effects of GC exposure on peripheral tissues are determined not only by the amount of the adrenal GC production but also by the peripheral GC metabolism [ 13 , 14 ] and by the GC sensitivity [ 15 ].…”
Section: Introductionmentioning
confidence: 99%